WATER-GAS SHIFT REACTION OVER THE POLYMETALIC Fe-CONTAINING SUPPORTED CATALYSTS - K.A. Valishevskiy,; S.S. Itkulova,; Y.A. Boleubaev, (Academic Scientific Journal of Chemistry, 2019)
The water-gas shift reaction over the polymetallic iron-containing catalysts modified by additives of the transition metals and supported on alumina was studied in the work. The effects of process temperature and nature of additives (Co or Cu) on behavior of the iron-containing catalysts in the process of interaction between water and carbon monoxide were investigated. It was observed that the synthesized iron-based catalysts modified by additives of copper/cobalt and transition metal of the 8th group of elements as the third component and supported on alumina perform the high activity and selectivity on hydrogen formation in the water-gas shift reaction. The optimum conditions for producing hydrogen by the water shift reaction over the synthesized catalysts are determined.